Reactive power capability of DFIG based wind turbine around synchronous operating point with two-level and three-level NPC converter - Sujod, Muhamad Zahim; Erlich, Istvan (2013 IEEE Grenoble PowerTech, 2013)
The increasing in wind turbines (WTs) generation system required grid utilities to extend its ability not only to provide active power but also having reactive power capability to fulfill transmission system requirements. The reactive power capability is subject to several limitations which change with the operating point. In doubly fed induction generator (DFIG) based WT, a special attention around synchronous operating point is needed since the limitation of maximum junction temperature of switching devices cause a reduction on maximum permissible output current at the rotor side. This paper investigates the reactive power capability of the DFIG with three-level neutral point clamped (NPC) voltage source converter (VSC) and provides a comparison with two-level VSC. The thermal behavior of the converters using semiconductor losses and thermal model are illustrated. Simulation results show that three-level NPC converter increased the maximum permissible rotor current as well as the reactive power capability of the DFIG.